IBOR Reform – Impact on Financial Instruments Valuation - Stránský, Roman (2021)
The goal of this thesis is to analyze the impact of ongoing reform of reference rates on financial instruments valuation. For this purpose, it is divided into four chapters. Gradually, reference rates before reform, problems leading to call for the reform, milestones in reform and alternative reference rates are introduced. Finally, properties of these rates are examined on historical time series and model examples of certain instruments valuation. Thesis confirms greater resistance of alternative reference rates to manipulation as well as their greater resiliency in periods of financial distress. The key finding is different price sensitivity to interest rate risk of instruments linked to alternative reference rate or to current reference rate. Consequently, the reform can impact no only valuation of instruments themselves, but also related capital requirement for market risk.